Rapid Decline in HIV Incidence Among Persons Who Inject Drugs During a Fast-Track Combination Prevention Program After an HIV Outbreak in Athens. (12th April 2017) - Sypsa, Vana; Psichogiou, Mina; Paraskevis, Dimitrios; Nikolopoulos, Georgios; Tsiara, Chrissa; Paraskeva, Dimitra; Micha, Katerina; Malliori, Meni; Pharris, Anastasia; Wiessing, Lucas; Donoghoe, Martin; Friedman, Samuel; et al.
Abstract: Background: A "seek-test-treat" intervention (ARISTOTLE) was implemented in response to an outbreak of human immunodeficiency virus (HIV) infection among persons who inject drugs (PWID) in Athens. We assess trends in HIV incidence, prevalence, risk behaviors and access to prevention/treatment. Methods: Methods included behavioral data collection, provision of injection equipment, HIV testing, linkage to opioid substitution treatment (OST) programs and HIV care during 5 rounds of respondent-driven sampling (2012–2013). HIV incidence was estimated from observed seroconversions. Results: Estimated coverage of the target population was 88% (71%–100%; 7113 questionnaires/blood samples from 3320 PWID). The prevalence of HIV infection was 16.5%. The incidence per 100 person-years decreased from 7.8 (95% confidence interval, 4.6–13.1) (2012) to 1.7 (0.55–5.31) (2013; P for trend = .001). Risk factors for seroconversion were frequency of injection, homelessness, and history of imprisonment. Injection at least once daily declined from 45.2% to 18.8% ( P < .001) and from 36.8% to 26.0% ( P = .007) for sharing syringes, and the proportion of undiagnosed HIV infection declined from 84.3% to 15.0% ( P < .001). Current OST increased from 12.2% to 27.7% ( P < .001), and 48.4% of unlinked seropositive participants were linked to HIV care through 2013. Repeat participants reported higher rates of adequate syringe coverage, linkage to HIV care and OST. Conclusions: Multiple evidence-based interventions delivered through rapid recruitment in a large proportion of the population of PWID are likely to have helped mitigate this HIV outbreak.